Bulinus sp : Molecular epidemiology, genetic structure and phylogeny in three African countries: Interaction with the Schistosoma genus - (:unkn) unknown (My University, 2014)
The Bulinus genus acts as intermediate hosts for larval development of the parasite belonging to Schistosoma group (Digenea, Platyhelminthes). Despite their importance in the transmission of these parasites, the evolutionary history of this genus is still not very clear. Development of management plans to control these parasites transmission requires a deeper understanding of the past events that have affected the population diversity and distribution of Bulinus species. The objective of this study was to learn more about the population structure and phylogeny of several Bulinus species originating from different African countries using three types of molecular markers: the partial mitochondrial gene Cox1, the nuclear ribosomal gene (ITS, 18S and 28S), and six microsatellites loci. Concerning the phylogeography of this genus, high levels of genetic diversity were detected in the seven studied species, with clear segregation between individuals and the presence of many haplotypes, even within same species from the same locality. Our results showed lower diversity within B. truncatus populations in North Africa (Egypt) compared to individuals from Sub-Saharan Africa, which may suggest that B. truncatus may have colonized Egypt from Sub-Saharan Africa. About the genetic structure of B. truncatus, high rate of heterozygosity, and strong genetic structure were noted in Egyptian populations of B. truncatus. This structure is reflected by the existence of four distinct clusters characterized by relatively low gene flew rate between subpopulations. Our work allowed better understanding of phylogeny and genetic structure of this genus. These informations can be used to develop new approach for controlling the parasite transmission.
Keywords: African Research